2020
DOI: 10.1103/physrevb.102.134113
|View full text |Cite
|
Sign up to set email alerts
|

Guiding shear bands in bulk metallic glasses using stress fields: A perspective from the activation of flow units

Abstract: Controlling shear band propagation is the key to obtain ductile metallic glasses. Here, we use a residual stress field to vary the direction of shear band propagation. We ascribe this behavior to the effect of the stress field on the activation of shear transformation zones (STZs) along their characteristic direction and we quantify this contribution to the energy of the process. Because of the progressively adverse orientation of the stress field, the energy stored as shear in the STZ decreases to a level whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
(59 reference statements)
3
3
0
Order By: Relevance
“…1a and c, the elastic strains parallel and perpendicular to the loading direction ( 11 and 22 ) display a highly heterogeneous profile that seems to be stabilized even after releasing the external load. This behavior indicates a highly inhomogeneous deformation mechanism, i.e., shear banding [24,28,29] and, hence, it further confirms that, at low temperature, the shear bands are the only plastic carriers in MGs. HAADF-STEM images of random selected-areas along the shear fronts (of highest volumetric strain) and between the notch area highlight shear band activity.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…1a and c, the elastic strains parallel and perpendicular to the loading direction ( 11 and 22 ) display a highly heterogeneous profile that seems to be stabilized even after releasing the external load. This behavior indicates a highly inhomogeneous deformation mechanism, i.e., shear banding [24,28,29] and, hence, it further confirms that, at low temperature, the shear bands are the only plastic carriers in MGs. HAADF-STEM images of random selected-areas along the shear fronts (of highest volumetric strain) and between the notch area highlight shear band activity.…”
Section: Introductionsupporting
confidence: 66%
“…It is well accepted that shear banding is not only confined to a narrow thin layer of about 20 nm but extends over a longer range (tens of micrometers) across the shear band [31,35,36]. Experimental observations of high-energy XRD across an individual shear band revealed that the strain at opposite sides of a shear band changes sign from compressive to tensile [24,29,31]. Likewise, the strains/stresses are created in an inhomogeneous manner during triaxial compression (see Fig.…”
Section: S2mentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic length scale is also commensurate with the critical size of soft regions that are responsible for triggering plastic shear transformations under thermal and/or mechanical stimuli. This is expected since the robust correlation between ΔQ and shear transformation has been well reported in the literature Kosiba et al (2020), Han et al (2020), andWei et al (2019). In this connection, local regions with a high level of S i can be identified as potential glassy defects.…”
Section: Structure-property Relationship Based On Ergodic Shannon Ent...supporting
confidence: 61%
“…Monolithic BMGs show limited plasticity at room temperature due to the fact that plastic deformation in these materials occurs via the formation and propagation of highly localized shear bands [2]. Kosiba et al [40] reported that shear band propagation in ZrCu-based glassy specimens can be guided via the generation of designed elastic stress fields, suggesting that the current BMG may be made ductile. BMG composites containing secondary phases in the glassy matrix is another effective way to toughen the monolithic glass via a mechanism of shear band arrest and multiplication [41].…”
Section: Discussionmentioning
confidence: 99%